Dampak Penggunaan Gadget Terhadap Aktivitas Fisik dan Tingkat Stres pada Siswa SMAN 1 Parongpong - Zaky Haidar Firmansyah; Asep Sumpena; Yudy Hendrayana (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
This study aimed to analyze the effect of gadget use on physical activity and stress levels among students of SMAN 1 Parongpong. A quantitative approach with an explanatory survey design was employed, involving 320 respondents selected from a population of 1,459 students through proportional random sampling based on grade level. Gadget use was measured using the Smartphone Addiction Scale-Short Version (SAS-SV), physical activity using the International Physical Activity Questionnaire-Short Form (IPAQ-SF), and stress levels using the Perceived Stress Scale 10 (PSS-10), with data analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) via SmartPLS 4.0. The results showed that most students (54%) were classified as addicted to gadgets, the majority had low physical activity levels (67.5%), and the majority experienced severe stress (60%). Bootstrapping hypothesis testing revealed that gadget use had a significant negative effect on physical activity (β = -0.780; t = 39.436; p = 0.000) and a significant positive effect on stress levels (β = 0.824; t = 46.668; p = 0.000), with the model explaining 60.9% of the variance in physical activity and 68.0% in stress levels. This study concludes that higher gadget use among students is associated with lower physical activity and higher stress levels, indicating the need for promotive interventions such as limiting gadget use during school hours and scheduled physical activity programs to balance technology use with students' physical and mental health. Keywords: Physical Activity, Gadget Use, PLS-SEM, High School Students, Stress Level